ICT-Training Initiative and Workforce Productivity Re-Invention in Edo State Universal Basic Education Board (2016-2019) - Mustapha, Adesoye Isiaka; Okonmah, Emmanuel Ifechukwude; Jesuhovie, Gideon (NIU Journal of Humanities, 2022)
Information Communication Technology (ICT) as one of the pillars of contemporary modernization has touched almost all areas of human endeavours. The rapid development of new technologies built around ICT initiatives has brought about organizational and behavioural change especially in the educational sector, where new technologies are deployed in the process of knowledge transfer. As a focal point in the process of knowledge transfer, teachers' capacity in ICT handling is paramount. With the Edo Basic Education Sector Transformation (EdoBEST) initiative, primary school teachers' handling of ICT facilities was addressed via compulsory training. In view of the above, the paper examined the level of workforce engagement via ICT training for optimum productivity in EDO SUBEB, and also to investigate the barriers to effective workforce ICT training for maximum productivity in EDO SUBEB. The paper adopted the qualitative research method via the medium of semi-structured interview in gathering relevant data for the study. The study discovered amongst others that, younger EdoBEST teachers were more open to the ICT training initiative, the study also noted that, new model of teaching was introduced to the teachers during the EdoBEST training for optimum productivity. The study thus recommends amongst others that, the training of EdoBEST teachers should be a continuous process in order to stay informed with modern educational practices.     Keywords: Workforce, ICT-training, productivity, EdoBEST, absenteeism, workers turnover.